PENGARUH LATIHAN E-MOVEMENT CONE DRILL TERHADAP KELINCAHAN PEMAIN FUTSAL SMPN 3 BANJARBARU - Mita Erliana; arisman arisman (Lambung Mangkurat University, 2017)
This study aims to determine the effect of exercise E-Movement Cone Drill Against Agility Futsal Player SMPN 3 Banjarbaru. The method used in this research that used quasi-experimental method (quasi-experimental research) with data collection techniques through tests.The study population was who following the extracurricular futsal in SMPN 3 Banjarbaru totaling 24 people. While taken as the sample in this study consisted of 15 people by using purposive sampling or sampling with consideration. A conclusion of the study in the know: there is exercise E-Movement Cone Drill influence on the Agility Futsal Player SMPN 3 Banjarbaru. Keywords: Effect, Agility, Exercise E-Movement Cone Drill